Candida parapsilosis Colony Morphotype Forecasts Biofilm Formation of Clinical Isolates - Emilia Gómez-Molero; Iker De-la-Pinta; Jordan Fernández-Pereira; Uwe Groß; Michael Weig; Guillermo Quindós; Piet W. J. de Groot; Oliver Bader (Journal of Fungi, 2021)
Candida parapsilosis is a frequent cause of fungal bloodstream infections, especially in critically ill neonates or immunocompromised patients. Due to the formation of biofilms, the use of indwelling catheters and other medical devices increases the risk of infection and complicates treatment, as cells embedded in biofilms display reduced drug susceptibility. Therefore, biofilm formation may be a significant clinical parameter, guiding downstream therapeutic choices. Here, we phenotypically characterized 120 selected isolates out of a prospective collection of 215 clinical C. parapsilosis isolates, determining biofilm formation, major emerging colony morphotype, and antifungal drug susceptibility of the isolates and their biofilms. In our isolate set, increased biofilm formation capacity was independent of body site of isolation and not predictable using standard or modified European Committee on Antimicrobial Susceptibility Testing (EUCAST) drug susceptibility testing protocols. In contrast, biofilm formation was strongly correlated with the appearance of non-smooth colony morphotypes and invasiveness into agar plates. Our data suggest that the observation of non-smooth colony morphotypes in cultures of C. parapsilosis may help as an indicator to consider the initiation of anti-biofilm-active therapy, such as the switch from azole- to echinocandin- or polyene-based strategies, especially in case of infections by potent biofilm-forming strains.